PENGGUNAAN KAJANG DALAM RITUS KEMATIAN (KELEPASAN) KLEN BRAHMANA BUDDHA DI DESA BUDAKELING DAN SEBARANNYA DI DESA BATUAN - Adnya Gentorang, Ida Made (Humanis; Volume 15. No.3. Juni 2016, 2016)
K ajang are part of the structure of the script and diagrams tattoo structured into a pattern and have a relationship. Buddhist Brahmin clan in the village Budakeling awning kajang masutasoma have only used by the Reverend Buddha in order rite of death (deliverance). Kajang masutasoma has a function as a means of purification atma (soul/spirit) to attain liberation (moksa). However, a change in the rite of death (deliverance) on the distribution of Buddhist Brahmins contained in Batuan village, which does not use the awning masutasoma, and proceed with the ceremony Maligia/Ngasti that are not on the Brahmin Buddhist village Brahmin clan Budakeling as a Buddhist center. This is due to the interaction of culture, causing the intervention of the majority in the village of Batuan.
Keywords: Kajang, rite, deliverance